The bioavailability of selenium and risk assessment for human selenium poisoning in high-Se areas, China - Qin, Hai-bo; Zhu, Jian-ming; Liang, Liang; Wang, Ming-shi; Su, Hui (Environment international, 2013)
Enshi prefecture of Hubei Province is well known for human selenium (Se) poisoning in the early 1960s in China. Sporadic cases of Se poisoning in livestocks are still being found. In this study, Se levels in water, cropland soils and various crops from high-Se areas of Enshi were measured to investigate the distribution and bioavailability of Se in the environments, as well as probable daily intake (PDI) of Se for local residents. The total Se in surface water ranged from 2.0 to 519.3μg/L with a geometric mean of 46.0±127.8μg/L (n=48), 70.5–99.5% of which was present in the form of Se(VI). The soil Se concentration varied from 2.89 to 87.3μg/g with a geometric mean of 9.36±18.6μg/g (n=45), and most of Se was associated with organic matter (OM-Se). The total Se in rice, corn, and vegetable samples were 2.11±2.87μg/g (n=21), 3.76±11.6μg/g (n=16), and 2.09±3.38μg/g (n=25), respectively. Stream water Se is likely leached from carbonaceous shale and mine wastes, leading to Se accumulation in paddy soils. OM-Se may play an important role in Se uptake by rice plant in high-Se area of Enshi. The PDI of Se is approximately 2144μg/day, and Se concentration in blood is estimated at about 3248μg/L, posing a potential chronic Se poisoning risk to local residents. Cereal consumption (48.5%) makes a great contribution to human daily Se intake, followed by vegetables (36.6%), meats (8.5%), and drinking water (6.4%). However, when assessing health risk on human in high-Se areas, the contribution of drinking water to daily Se intake cannot be ignored due to high Se content and dominant Se(VI) species. Local inhabitants should be advised not to grow crops in high-Se lands or irrigate using high-Se water. If possible, they should drink pipe water and consume foods mixed with those from outside the high-Se areas. ► Selenium in surface water derives from the leaching of Se-rich rocks and mine waste dumps. ► OM-Se is the predominant fraction in paddy soils of high-Se areas in Enshi. ► The daily Se intake is estimated at 2144μg/day, posing a potentially chronic selenosis risk to local people. ► Cereal consumption makes a great contribution to daily Se intake. ► Drinking water cannot be ignored to estimate daily Se intake in high-Se areas of China.